Dose-escalation study with supplemental creatine-guanidinoacetate in healthy adults - Ostojic, Sergej; Farkas , Gábor; Bábszky , Zsófia; Stajer, Valdemar (Progress in Nutrition, 2024)
Background and aim: A co-administration of creatine and guanidinoacetate (GAA) emerges as a promising dietary intervention yet limited information is currently available regarding its safety for dose-escalating studies. In this open-label pilot study, we assessed the impact of escalating doses of supplemental creatine-GAA on total homocysteine levels (T-Hcy) in the plasma of healthy adultsMethods:Eight young, physically active volunteers (age 22.5 ± 2.2 years, weight 64.1 ± 10.8 kg, height 165.4 ± 7.1; six females) provided informed consent to receive three escalating doses of the mixture, each administered for four weeks.Results:One-way ANOVA analysis revealed no significant differences in mean T-Hcy levels across the study (P = 0.76). Moreover, no cases of hyperhomocysteinemia (T-Hcy > 15 µmol/L) were observed during the study period.Conclusions: These findings suggest that the mixture is generally well-tolerated when administered up to three grams each of creatine and GAA over a three-month dose-escalating protocol in healthy adults, with no significant increase in homocysteine levels.